Retail Internationalization Analysis of Market Entry Modes, Format Transfer and Coordination of Retail Activities - Elsner, Stefan. (Handel und Internationales Marketing Retailing and International Marketing,, 2014)
Retail internationalization is gaining importance in retail practice, but the research status is still fairly narrow. Stefan Elsner aims to close this gap by investigating three important challenges within the retail internationalization process: the appropriate choice of market entry modes, the successful retail format transfer and the successful organizational structure abroad. Based on substantial macro-economic data and comprehensive interviews with retail firms operating internationally, the results emphasize the necessity of an established frame that provides the general direction, but leaves enough room for adaptations. Based on this finding, important implications can be drawn for research and practice.   Contents ·         Entry Mode Choice ·         Format Transfer ·         Standardization and Adaptation ·         Organizational Structure   Target Groups  ·         Researchers and students of business administration with majors in marketing and international management. ·         Executives, managers and experts in the area of corporate management, international expansion and subsidiary management.   About the author Dr. Stefan Elsner worked as a research and teaching associate at the Chair of Marketing and Retailing at the University of Trier.